2020
DOI: 10.22146/ijc.48806
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Capped with <i>p</i>-Hydroxybenzoic Acid as a Colorimetric Sensor for the Determination of Paraquat

Abstract: Highly stable silver nanoparticles capped with p-hydroxybenzoic acid were synthesized by reducing silver ion with p-hydroxybenzoic acid and used for the detection of paraquat. The synthesized silver nanoparticles, which are yellow, exhibited an absorption peak at 420 nm when measured with a UV-visible spectrophotometer due to the surface plasmon resonance. In the presence of paraquat, the color of silver nanoparticles changed from yellow to purple accompanied by the appearance of a new peak at 580 nm in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…At silver concentrations of 2×10 -4 M and 3×10 -4 M, two measured wavelengths, namely 410 and 415 nm, were observed, accompanied by a broadening of the peak towards the redshift, indicative of larger nanoparticle sizes. This finding aligns with previous research by Gusrizal et al [19], which demonstrated an increase in absorbance intensity with rising silver concentration and a consequent increase in silver nanoparticle size. Therefore, a silver concentration of 1.5×10 -4 M was chosen for further synthesis.…”
Section: Figure 4 Surface Plasmon Resonance Spectra Of Silver Nanopar...supporting
confidence: 93%
“…At silver concentrations of 2×10 -4 M and 3×10 -4 M, two measured wavelengths, namely 410 and 415 nm, were observed, accompanied by a broadening of the peak towards the redshift, indicative of larger nanoparticle sizes. This finding aligns with previous research by Gusrizal et al [19], which demonstrated an increase in absorbance intensity with rising silver concentration and a consequent increase in silver nanoparticle size. Therefore, a silver concentration of 1.5×10 -4 M was chosen for further synthesis.…”
Section: Figure 4 Surface Plasmon Resonance Spectra Of Silver Nanopar...supporting
confidence: 93%
“…1a). This was evidenced by the formation of the characteristic surface plasmon resonance (SPR) absorbance band centered at 407 nm, commonly reported around 420 nm [39][40][41] , the lack of a band in the cellulose spectrum and visually, via color change (light yellow to black to grey), indicative of the redox reaction between the Ag salt and ascorbic acid (Fig. 1b).…”
Section: Resultsmentioning
confidence: 88%
“…Figure 4 a shows the UV–vis absorption spectra of the neat CNF film and the CNF-AgNP composite film, reflecting the successful formation of a AgNP. AgNPs formed from the redox reaction between the Ag + ions of AgNO 3 and NaBH 4 were revealed from the cellulose spectrum of the characteristic UV–vis absorption band generally in the 400–450 nm range, as well as from the visible yellow color change [ 21 , 22 , 23 ]. This color persisted in the CNF-AgNP compound for 3 months, indicating that the AgNPs synthesized on cellulose exhibit excellent stability [ 24 ].…”
Section: Resultsmentioning
confidence: 99%